Effect of Driver Behavior Effect of Driver Behavior on the Coal Truck Trips Movement on Coal Haul Roadson the Coal Truck Trips Movement on Coal Haul Roads - D. , Yuniar; L. , Djakfar; A. , Wicaksono; A. , Efendi (International Journal of Psychosocial Rehabilitation, 2020)
The pattern of coal hauling travel is highly dependent on driver behaviour. Drivers who have experiences and skills in driving big trucks on coal haul roads make them more comfortable during the trip. Good work motivation will reduce the driver habits wasting time traveling in certain places. The use of the right time will affect driver behavior, including rest, sleep, normal work and social contact. The research to analyze effect of driver behavior on truck trips movement and use of travel time on coal haul roads. The research methods are field study, observations, and questionnaires with analytical statistics. The results indicates that coal truck driver behavior very influenced by work-motivation, road and vehicle conditions. This directly affects the pattern of truck trips movement from the stockpile to the port. The stopping duration at certain places such as stalls, roadside and workshops causes the travel time duration to increase, thereby reducing timeliness. The good vehicle condition adds to the truck drivers work motivation. Damaged road conditions and excess loads increase alertness, are not comfortable, thereby reducing travel speed. Transportation companies and coal haul drivers must maintain the safety, smooth distribution of goods and periodic maintenance of vehicles to stay excellent.